Method for preparing simple carbon-anchored high-dispersion nano cobalt particles and removing antibiotics by activating peroxymonosulfate through simple carbon-anchored high-dispersion nano cobalt particles

By using carbon-anchored highly dispersed cobalt nanoparticles to activate persulfate, the problem of difficult degradation of antibiotics in water is solved, and efficient degradation and catalyst stability and recovery are achieved.

CN119500135APending Publication Date: 2025-02-25FUJIAN NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411416822.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently degrade antibiotics in water, especially sulfonamide antibiotics, and traditional water treatment processes have poor degradation effects.

Method used

Carbon-anchored highly dispersed cobalt nanoparticles (Con/C) are used as catalysts to activate PMS to enhance its oxidation capacity, thereby efficiently degrading antibiotics. The catalyst is made of sodium alginate and cobalt salt as raw materials, and is added dropwise through a peristaltic pump to form a hydrogel. The pellets are prepared by freeze-drying and high-temperature calcination.

Benefits of technology

It has achieved efficient degradation of various antibiotics, with a removal efficiency of more than 90% within 20 minutes, and the catalyst has good stability and recyclability, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500135A_ABST
    Figure CN119500135A_ABST
Patent Text Reader

Abstract

The invention discloses a simple preparation method of carbon-anchored high-dispersion cobalt nano-particles and a method for removing antibiotics by activating peroxymonosulfate through the carbon-anchored high-dispersion cobalt nano-particles. According to the preparation method, green, environment-friendly and considerable-cost sodium alginate is selected as a raw material, after the sodium alginate and cobalt ions are subjected to cross-linking curing, a round granular cobalt alginate aerogel precursor with the uniform size is prepared through cold drying, and the round granular cobalt alginate aerogel precursor is subjected to high-temperature calcination to synthesize the carbon-anchored high-dispersion cobalt nanoparticle composite material. By activating peroxymonosulfate, efficient degradation of antibiotics in wastewater can be realized. The material is simple in preparation method and excellent in catalytic performance, can degrade antibiotics in wastewater under a wide pH condition, and shows relatively high stability and circularity. The invention provides a green and low-cost method for preparing the heterogeneous peroxymonosulfate advanced oxidation catalyst, and the catalyst can be widely used for removing antibiotics and has very high application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of sewage and wastewater treatment, and in particular to the preparation of carbon-anchored highly dispersed cobalt nanoparticles and the use of activated peroxymonosulfate thereof for degrading and removing refractory organic matter in water. Background Art

[0002] In recent years, antibiotics have become an emerging pollutant that has attracted much attention. Among them, antibiotics have long been widely used to prevent or treat bacterial diseases in humans and animals, and are easy to migrate and transform in the environment. They can damage the immune system and accumulate in the environment, further triggering the growth and spread of antibiotic-resistant bacteria and antibiotic resistance genes, causing continuous damage to humans and ecosystems. Due to their poor biodegradability and strong antibacterial properties, traditional water treatment processes have poor degradation effects on them. Therefore, there is an urgent need to develop safe and effective water treatment technologies to achieve efficient degradation of sulfonamide antibiotics.

[0003] Sulfate radical-based advanced oxidation processes (SRs-AOPs) have been applied to treat some difficult-to-degrade pollutants due to their higher redox potential, better oxidation capacity, and wider pH adaptability. Peroxymonosulfate (PMS) has high activity in the SRs-AOPs process, but its oxidation efficiency is limited. Therefore, the key to the application of peroxymonosulfate-based advanced oxidation technology is to find a method to efficiently activate persulfate.

[0004] Transition metal-based materials are highly efficient catalysts for activating PMS. When transition metals come into contact with PMS, electron transfer occurs, destroying the peroxide bonds of PMS, generating active oxidizing substances, and enhancing activation. However, the disadvantages of transition metal-based materials, such as easy deactivation and agglomeration, limit their application in water treatment.

[0005] The complex of transition metal and carbon has become a promising candidate material for activating PMS. Some studies have shown that loading it on carbon-based materials such as biochar and MOFs derivatives can significantly improve the dispersibility of the active components. Therefore, loading transition metals on carbon substrates is an effective strategy to improve the catalytic activity and stability of materials, especially cobalt-carbon composite materials, which not only exert the good catalytic activity of the cobalt base itself, but also wrap the metal with different degrees of graphitization of carbon, further improving the catalytic activity of the composite interface and enhancing the stability of the catalyst. Hu Xun et al. used vanillin, furfural, organic acid and cobalt salt as raw materials, and obtained cobalt-carbon catalyst after solvent thermal and high-temperature calcination (a preparation method for preparing cobalt-carbon catalyst by polymerization reaction and its application CN113332984 A), Zhan Tianrong et al. used metal organic framework compound Co(OBDC) as a precursor and prepared cobalt-carbon porous oxygen reduction electrocatalyst by high-temperature calcination (a cobalt-carbon porous nanocomposite oxygen reduction electrocatalyst and its preparation method and application CN106410224 A). Zhong Xuexin et al. doped cobalt ions into MIL-53 (Al) and applied it to activate PMS to treat antibiotic wastewater (method for treating antibiotic wastewater using a system consisting of cobalt ion-doped metal organic framework materials and PMS CN112062256A). The raw materials and preparation methods involved in the above methods may be relatively complicated, or the working concentration of PMS is relatively high, and there is a problem of limited activation efficiency. In order to solve the existing problems, this patent uses cobalt salt as the cobalt source and sodium alginate, a green and cheap carbon source, to fix and disperse cobalt ions to form a gel three-dimensional network structure as a precursor. After high-temperature calcination, carbon-anchored highly dispersed cobalt nanoparticles are prepared, and used to enhance the activation of PMS to efficiently degrade antibiotics in aquaculture wastewater. Summary of the invention

[0006] In view of the above-mentioned problem of removing antibiotic wastewater by advanced oxidation, the present invention provides a carbon-anchored highly dispersed cobalt nanoparticle (Co n / C), and use it to activate peroxymonosulfate to remove antibiotics. The catalyst preparation of this method is simple, efficient and feasible, with high catalytic activity, fast pollutant degradation rate and easy catalyst recovery.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is a method for preparing carbon-anchored highly dispersed cobalt nanoparticles and activating peroxymonosulfate to remove antibiotics, and the specific steps are as follows:

[0008] S1: Use a peristaltic pump to evenly add the sodium alginate solution to the cobalt ion (Co 2+) solution. In this step, spherical particles, namely Co-SA hydrogel beads, are formed. After stabilization in the solution for 24 hours, the Co-SA hydrogel beads are rinsed with deionized water to completely remove unbound cobalt ions. Then, they are frozen in a refrigerator (-20°C) for 30 minutes, and immediately freeze-dried in a vacuum for 24 hours after freezing to obtain Co-SA aerogel.

[0009] S2: The Co-SA aerogel was calcined in a N2 atmosphere at different temperatures with a heating rate of 5°C / min and ground to obtain carbon-anchored highly dispersed cobalt nanoparticles. The XRD results are shown in Figure 1 shown.

[0010] S3: Add PMS to simulated antibiotic wastewater containing antibiotics and adjust the pH, add 0.025g / L Co n / C wherein, stirring is continued, and after 20 minutes, the degradation of the antibiotic is completed.

[0011] Preferably, the mass fraction of the sodium alginate solution is 0.5%-5.0%.

[0012] Preferably, the flow rate of the peristaltic pump is 1.0-5.0 mL / min.

[0013] Preferably, the Co-SA aerogel is calcined at a temperature of 450-950°C.

[0014] Preferably, the Co-SA aerogel is calcined for 0.5-2 h.

[0015] Preferably, the peroxymonosulfate concentration is 0.02-0.2 mmol / L.

[0016] Preferably, the pH of the simulated antibiotic wastewater is 3.0-9.0

[0017] Optionally, the simulated antibiotic wastewater concentration is 1-20 mg / L

[0018] Optionally, the antibiotics in the simulated antibiotic wastewater are sulfamethoxazole, sulfamethoxazole, tetracycline and ofloxacin, etc.

[0019] The present invention has the following advantages and outstanding technical effects

[0020] (1) Sodium alginate, which is green and cost-effective, was used as a template to effectively fix and disperse cobalt ions in a relatively simple way. As a precursor of highly dispersed cobalt / carbon composite catalyst, a method for preparing carbon-anchored highly dispersed cobalt nanoparticles was provided. n / C) are mainly nano-sized and micro-sized cobalt particles (such as Figure 2SEM shows), good stability and high catalytic performance. The method has the advantages of simple and convenient preparation method, few types of raw materials required, low cost, high yield, etc., and is suitable for large-scale preparation.

[0021] (2) Carbon-anchored highly dispersed cobalt nanoparticles have the characteristics of highly efficient degradation of antibiotics, and can maintain a removal efficiency of more than 90% for a variety of antibiotics within 20 minutes.

[0022] (3) The present invention optimizes sodium alginate, cobalt ion concentration, and calcination temperature to obtain a suitable catalytic material and improve its catalytic performance in activating PMS to degrade antibiotics.

[0023] (4) The carbon-anchored highly dispersed cobalt nanoparticles have high stability and can be recycled and reused multiple times. After six cycles, the removal efficiency of sulfamethoxazole is still higher than 84%. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is the XRD pattern of carbon-anchored highly dispersed cobalt nanoparticles.

[0025] Figure 2 is the SEM image of carbon-anchored highly dispersed cobalt nanoparticles.

[0026] Figure 3 The efficiency of removing antibiotics by activating peroxymonosulfate using carbon-anchored highly dispersed cobalt nanoparticles

[0027] Figure 4 This is the efficiency diagram of removing antibiotics by activating persulfate with carbon-anchored highly dispersed cobalt nanoparticles for multiple cycles.

[0028] The specific implementation modes of the present invention will be further described in detail below in conjunction with the accompanying drawings. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is clearly and detailedly described below with reference to examples.

[0030] Example 1

[0031] A method for preparing simple carbon-anchored highly dispersed cobalt nanoparticles and activating peroxymonosulfate to remove antibiotics comprises the following steps:

[0032] S1: A 2.5% sodium alginate solution was added dropwise to a 0.3 mol / L CoCl2 solution at a flow rate of 3.5 mL / min using a peristaltic pump while continuously stirring. In this step, spherical particles, namely Co-SA hydrogel beads, were gradually formed. After stabilization in the CoCl2 solution for 24 hours, the Co-SA hydrogel beads were rinsed with deionized water to completely remove unbound cobalt ions, and then frozen in a refrigerator (-20°C) for 30 minutes. After freezing, they were immediately vacuum-freeze-dried for 24 hours to obtain Co-SA aerogel. S2: The Co-SA aerogel was calcined at 900 °C for 2 h in a N2 atmosphere at a heating rate of 5 °C / min, and ground to obtain a carbon-anchored highly dispersed cobalt nanoparticle composite material (Co n / C). S3: PMS (0.1 mmol / L) was added to the simulated antibiotic wastewater containing 10 mg / L sulfamethoxazole and the pH was adjusted to 7.0. n / C dosage was 0.025 g / L, stirring was continued, and liquid chromatography was used to test the concentration change of sulfamethoxazole in the reaction. The reaction time was 20 min.

[0033] In this embodiment, the removal efficiency of sulfamethoxazole can reach 96%, and the first-order reaction kinetic constant k obs =0.529min -1 Considering the catalyst dosage, PMS concentration and treated pollutant concentration, the modified kinetic constant k-value is 2001.74min -1 mol -1

[0034] Example 2

[0035] A method for preparing simple carbon-anchored highly dispersed cobalt nanoparticles and activating peroxymonosulfate to remove antibiotics comprises the following steps:

[0036] S1: A 2.5% sodium alginate solution was added dropwise to a 0.3 mol / L CoCl2 solution at a flow rate of 3.5 mL / min using a peristaltic pump while continuously stirring. In this step, spherical particles, namely Co-SA hydrogel beads, were gradually formed. After stabilization in the CoCl2 solution for 24 hours, the Co-SA hydrogel beads were rinsed with deionized water to completely remove unbound cobalt ions, and then frozen in a refrigerator (-20°C) for 30 minutes. After freezing, they were immediately vacuum-freeze-dried for 24 hours to obtain Co-SA aerogel. S2: The Co-SA aerogel was calcined at 900 °C for 2 h in a N2 atmosphere at a heating rate of 5 °C / min, and ground to obtain a carbon-anchored highly dispersed cobalt nanoparticle composite material (Co n / C). S3: PMS (0.1 mmol / L) was added to the simulated antibiotic wastewater containing 10 mg / L sulfamethoxazole and the pH was adjusted to 5.0. n / C dosage was 0.025 g / L, stirring was continued, and liquid chromatography was used to test the concentration change of sulfamethoxazole in the reaction. The reaction time was 20 min.

[0037] In this embodiment, the removal efficiency of sulfamethoxazole can reach 91%.

[0038] Example 3

[0039] A method for preparing simple carbon-anchored highly dispersed cobalt nanoparticles and activating peroxymonosulfate to remove antibiotics comprises the following steps:

[0040] S1: A 2.5% sodium alginate solution was added dropwise to a 0.3 mol / L CoCl2 solution at a flow rate of 3.5 mL / min using a peristaltic pump while continuously stirring. In this step, spherical particles, namely Co-SA hydrogel beads, were gradually formed. After stabilization in the CoCl2 solution for 24 hours, the Co-SA hydrogel beads were rinsed with deionized water to completely remove unbound cobalt ions, and then frozen in a refrigerator (-20°C) for 30 minutes. After freezing, they were immediately vacuum-freeze-dried for 24 hours to obtain Co-SA aerogel. S2: The Co-SA aerogel was calcined at 900 °C for 2 h in a N2 atmosphere at a heating rate of 5 °C / min, and ground to obtain a carbon-anchored highly dispersed cobalt nanoparticle composite material (Co n / C). S3: PMS (0.2 mmol / L) was added to the simulated antibiotic wastewater containing 10 mg / L sulfamethoxazole and the pH was adjusted to 7.0. n / C dosage was 0.025 g / L, stirring was continued, and liquid chromatography was used to test the concentration change of sulfamethoxazole in the reaction.

[0041] In this embodiment, the removal efficiency of sulfamethoxazole can reach 97%.

[0042] Example 4

[0043] A method for preparing simple carbon-anchored highly dispersed cobalt nanoparticles and activating peroxymonosulfate to remove antibiotics comprises the following steps:

[0044] S1: Use a peristaltic pump to drop a 2% sodium alginate solution into a 0.3 mol / L CoCl2 solution at a flow rate of 3.5 mL / min while stirring continuously. In this step, spherical particles, namely Co-SA hydrogel beads, are gradually formed. After stabilization in the CoCl2 solution for 24 hours, the Co-SA hydrogel beads are rinsed with deionized water to completely remove unbound cobalt ions, and then frozen in a refrigerator (-20°C) for 30 minutes. After freezing, they are immediately vacuum-freeze-dried for 24 hours to obtain Co-SA aerogel. S2: The Co-SA aerogel was calcined at 500°C for 2 h in a N2 atmosphere with a heating rate of 5°C / min, and then ground to obtain carbon-anchored highly dispersed cobalt nanoparticles. S3: PMS (0.1 mmol / L) was added to the simulated antibiotic wastewater containing 10 mg / L sulfamethoxazole and the pH was adjusted to 7.0. n / C dosage was 0.025 g / L, stirring was continued, and liquid chromatography was used to test the concentration change of sulfamethoxazole in the reaction. The reaction time was 20 min.

[0045] In this embodiment, the removal efficiency of sulfamethoxazole can reach 95.5%.

[0046] Example 5

[0047] S1: A 2.5% sodium alginate solution was added dropwise to a 0.3 mol / L CoCl2 solution at a flow rate of 3.5 mL / min using a peristaltic pump while continuously stirring. In this step, spherical particles, namely Co-SA hydrogel beads, were gradually formed. After stabilization in the CoCl2 solution for 24 hours, the hydrogel beads were rinsed with deionized water to completely remove unbound cobalt ions, and then frozen in a refrigerator (-20°C) for 30 minutes. After freezing, they were immediately vacuum-freeze-dried for 24 hours to obtain Co-SA aerogel. S2: The Co-SA aerogel was calcined at 900°C for 2 h in a N2 atmosphere at a heating rate of 5°C / min, and then ground to obtain carbon-anchored highly dispersed cobalt nanoparticles. S3: PMS (0.1 mmol / L) was added to the simulated antibiotic wastewater containing 10 mg / L tetracycline and the pH was adjusted to 7.0. n / C dosage was 0.025 g / L, stirring was continued, and liquid chromatography was used to test the concentration change of tetracycline in the reaction. The reaction time was 20 min.

[0048] In this embodiment, the removal efficiency of tetracycline can reach 100%.

[0049] Example 6

[0050] A method for preparing simple carbon-anchored highly dispersed cobalt nanoparticles and activating peroxymonosulfate to remove antibiotics comprises the following steps:

[0051] S1: A 2.5% sodium alginate solution was added dropwise to a 0.3 mol / L CoCl2 solution at a flow rate of 3.5 mL / min using a peristaltic pump while continuously stirring. In this step, spherical particles, i.e., Co-SA hydrogel beads, were gradually formed. After stabilization in the CoCl2 solution for 24 hours, the Co-SA hydrogel beads were rinsed with deionized water to completely remove unbound cobalt ions, and then frozen in a refrigerator (-20°C) for 30 minutes. After freezing, they were immediately vacuum-freeze-dried for 24 hours to obtain Co-SA aerogel. S2: The Co-SA aerogel was calcined at 900 °C for 2 h in a N2 atmosphere at a heating rate of 5 °C / min, and ground to obtain a carbon-anchored highly dispersed cobalt nanoparticle composite material (Co n / C). S3: PMS (0.1 mmol / L) was added to the simulated antibiotic wastewater containing 10 mg / L sulfamethoxazole and the pH was adjusted to 7.0. n The dosage of / C was 0.025g / L, stirring was continued, and the concentration change of sulfamethoxazole in the reaction was tested by liquid chromatography. The reaction time was 20min. After the reaction was completed, a vacuum pump was used to filter and recover Co n / C, keeping the dosage unchanged, re-adding it to the simulated antibiotic wastewater with 10 mg / L sulfamethoxazole added with PMS (0.1 mmol / L), keeping the reaction time unchanged, and thus repeatedly using the material to degrade sulfamethoxazole.

[0052] In this embodiment, the removal efficiency of sulfamethoxazole in any cycle is higher than 84%.

[0053] Comparative Example 1

[0054] The method for removing antibiotics by activating peroxymonosulfate with commercial cobalt powder comprises the following steps:

[0055] S1: PMS (0.1mmol / L) was added to the simulated antibiotic wastewater containing 10mg / L sulfamethoxazole and the pH was adjusted to 7.0. The cobalt powder was added at a dosage of 0.025g / L. The mixture was stirred continuously and the concentration change of sulfamethoxazole in the reaction was tested by liquid chromatography. The reaction time was 20min. After the reaction, the commercial cobalt powder was completely dissolved in the wastewater and could not be recycled.

[0056] In this comparative example, the removal rate of sulfamethoxazole is 90%, but the cobalt powder has poor stability and cannot be recycled.

[0057] Comparative Example 2

[0058] The method for removing antibiotics by activating peroxymonosulfate with cobalt tetraoxide (Co3O4) comprises the following steps:

[0059] S1: PMS (0.1 mmol / L) was added to the simulated antibiotic wastewater containing 10 mg / L sulfamethoxazole and the pH was adjusted to 7.0. The Co3O4 dosage was 0.025 g / L (with 0.01 g / L Co n / C) and continued stirring. The concentration change of sulfamethoxazole in the reaction was tested by liquid chromatography. The reaction time was 20 min.

[0060] The removal rate of sulfamethoxazole in this comparative example is only 39%, which is relatively low in efficiency.

[0061] Comparative Example 3

[0062] The method for removing antibiotics by activating peroxymonosulfate using calcium-based carbon materials prepared by calcium cross-linking comprises the following steps:

[0063] S1: Use a peristaltic pump to drop a 2.5% sodium alginate solution into a 0.3 mol / L CaCl2 solution at a flow rate of 3.5 mL / min to replace the cobalt ions while stirring continuously. In this step, spherical particles, i.e., Ca-SA hydrogel beads, are gradually formed. After stabilization in the CaCl2 solution for 24 hours, the Ca-SA hydrogel beads are rinsed with deionized water to completely remove unbound calcium ions, and then frozen in a refrigerator (-20°C) for 30 minutes. After freezing, they are immediately vacuum-freeze-dried for 24 hours to obtain Ca-SA aerogel. S2: The Ca-SA aerogel was calcined at 900°C for 2 h in a N2 atmosphere at a heating rate of 5°C / min, and then ground to obtain a calcium-based carbon material. S3: Add PMS (0.1 mmol / L) to the simulated antibiotic wastewater containing 10 mg / L sulfamethoxazole and adjust the pH to 7.0. The CaO / C dosage is 0.025 g / L. Stir continuously and use liquid chromatography to test the concentration change of sulfamethoxazole in the reaction. The reaction time is 20 min.

[0064] The removal rate of sulfamethoxazole in this comparative example was 12%, which was low in efficiency. The composite material prepared by calcium cross-linking in the same method failed to activate peroxymonosulfate.

[0065] The above descriptions are only embodiments of the present invention, and are not intended to limit the scope of the present invention. Any equivalent method or process change made using the contents of the present invention specification is not subject to the protection scope of the patent. The present invention involves a method for activating peroxymonosulfate to degrade antibiotics by synthesizing carbon-anchored highly dispersed cobalt nanoparticles, which involves the process of material preparation and activation of peroxymonosulfate to degrade antibiotics. All carbon-anchored highly dispersed cobalt nanoparticles and antibiotic degradation prepared based on different parameter conditions using this method fall within the scope of protection of the present invention. Within the scope described in the claims, a number of improvements and modifications may be made by those skilled in the art without creative labor, and these improvements and modifications shall be deemed as the scope of protection of the present invention.

Claims

1. A method for preparing simple carbon-anchored highly dispersed cobalt nanoparticles and activating peroxymonosulfate to remove antibiotics, comprising the following steps: S1: Sodium alginate solution is added dropwise to the continuously stirred cobalt ion (Co 2+ ) solution to form hydrogel spheres. After solidification in the solution for 24 hours, the Co-SA aerogel was formed after freezing for 30 minutes and vacuum freeze drying for 24 hours. S2: The Co-SA aerogel is calcined at a certain temperature in a nitrogen (N2) atmosphere at a heating rate of 5°C / min, and ground to obtain a carbon-anchored highly dispersed cobalt nanoparticle composite material. S3: After adding persulfate and carbon-anchored highly dispersed cobalt nanoparticle composites into simulated antibiotic wastewater with different pH values, the reaction was stirred continuously to activate persulfate through the material to degrade antibiotics in the water.

2. The method for preparing a simple carbon-anchored highly dispersed cobalt nanoparticle and activating peroxymonosulfate to remove antibiotics according to claim 1, characterized in that: In S1, 0.5-5% sodium alginate was used as a template and 0.05-0.5 mol / L cobalt ions (Co 2+ ) cross-linking, the solution of which is various inorganic cobalt salt solutions such as CoCl2, Co(NO3)2, etc.

3. The method for preparing a simple carbon-anchored highly dispersed cobalt nanoparticle and activating peroxymonosulfate to remove antibiotics according to claim 1, characterized in that: The calcination temperature of Co-SA aerogel in S2 in N2 atmosphere is 450-950°C and the calcination time is 0.5-2h.

4. The method for preparing a simple carbon-anchored highly dispersed cobalt nanoparticle and activating peroxymonosulfate to remove antibiotics as claimed in claim 1, characterized in that: The cobalt nanoparticles in the carbon-anchored highly dispersed cobalt nanoparticle composite material S2 are nanometer and micrometer scale with a few atoms.

5. The method for preparing a simple carbon-anchored highly dispersed cobalt nanoparticle and activating peroxymonosulfate to remove antibiotics as claimed in claim 1, characterized in that: The pH range of the simulated antibiotic wastewater in S3 was 3.0-9.0, and the addition concentration of permonosulfate was 0.02-0.2 mmol / L.

6. The method for preparing a simple carbon-anchored highly dispersed cobalt nanoparticle and activating peroxymonosulfate to remove antibiotics as claimed in claim 1, characterized in that: The antibiotics in the simulated antibiotic wastewater in S3 include at least one of sulfamethoxazole, sulfamethoxazole, ofloxacin, tetracycline, etc., with a concentration of 1-20 mg / L.

Citation Information

Patent Citations

  • Cobalt-carbon porous nanocomposite oxygen reduction electrocatalyst and its preparation method and application

    CN106410224A

  • Method for treating antibiotic wastewater by using system composed of cobalt ion doped metal organic framework material and PMS

    CN112062256A